Synchrony and diachrony of Okinawan Kakari Musubi in comparative perspective with premodern Japanese - Shinzato (Languages of Asia series, 2013)
Rumiko Shinzato and Leon A. Serafim bring a new dimension to 'kakari musubi' (a type of focus construction, henceforth KM) research, incorporating Japanese and Western linguistic theories, and synthesizing Okinawan and Japanese scholarship. Specifically, they analyze still-extant Okinawan KM in comparative perspective with its now extinct Japanese counterpart, while also offering reconstructed Proto-Japonic forms. Major hypotheses on the origins and demise of KM with insight from Okinawan are also evaluated. In addition, viewing KM as consisting of 'kakari' particle + nominalized 'musubi' predicate, they compare KM with its structural analogs, such as (1) Modern Japanese no-da, (2) its corollary in Japanese Western Periphery dialects, and (3) English it-clefts. Finally, the authors apply iconicity-based analyses and grammaticalization theory, interpreting correspondences between deictic-origin particles, which are shared, their epistemically unique musubi forms, and their respective functions.